Evaluation of Preclinical Efficacy of Curcumin-Loaded Bicosome Systems in Amelioration of Oral Mucositis - Daniela Vergara; Claudia Sanhueza; Susana Méndez; Mariela Bustamante; Benjamín Vega; Francisca Acevedo; Olga López (Pharmaceutics)
Background/Objectives: Oral mucositis (OM) is a common and debilitating side effect of cancer therapy, characterized by ulceration or inflammation of the oral mucosa. This study evaluates the preclinical efficacy of curcumin-loaded bicosome systems (cur-BS) in mitigating chemotherapy-induced OM in mice. Methods: BS were prepared using a combination of 1,2-di-palmitoyl-sn-glycero-3-phosphocholine (DPPC) and 1,2-dihexanoyl-sn-glycero-3-phosphocholine (DHPC), α-tocopherol, and curcumin, encapsulated within liposomal vesicles. Three formulations with different curcumin concentrations (180, 540, and 900 μM) were characterized by particle size, polydispersity index (PDI), encapsulation efficiency (EE), appearance, and morphology. The formulation with the highest concentration (cur-BS 5×) was selected for ex vivo permeability studies, release profile analysis, and in vitro anti-inflammatory efficacy. OM was induced in mice using 5-fluorouracil (5-FU) and acetic acid. Cur-BS 5× was compared to the commercial product Dentoxol®. Results: The results showed that cur-BS 5× provided sustained release through a mechanism involving both diffusion and matrix relaxation, enhancing curcumin retention in deeper skin layers. Treatment with cur-BS 5× downregulated the expression of inflammatory markers (IL-1β and TNF-α). Macroscopic assessments demonstrated that both cur-BS 5× and Dentoxol® reduced OM severity, with the greatest improvement observed between days 6 and 9. By day 24, OM scores were 1.25 ± 0.5 for cur-BS 5× and 1.0 ± 0.0 for Dentoxol®, indicating effectiveness in both treatments. However, histological analysis revealed superior tissue recovery with cur-BS 5×, showing better epithelial structure and reduced inflammation. Cur-BS 5×-treated mice also exhibited greater weight recovery and higher survival rates compared to the Dentoxol® group. Conclusions: These findings suggest that cur-BS 5× may enhance OM treatment, offering outcomes comparable to or better than those of Dentoxol®.